The effect of precursor concentration on the particle size, crystal size, and optical energy gap of cexsn1?xo2 nanofabrication - Al-Hada N.M.; Kasmani R.Md.; Kasim H.; Al-Ghaili A.M.; Saleh M.A.; Banoqitah E.M.; Alhawsawi A.M.; Baqer A.A.; Liu J.; Xu S.; Li Q.; Noorazlan A.M.; et al. (MDPI, 2023)
In the present work, a thermal treatment technique is applied for the synthesis of CexSn1?xO2 nanoparticles. Using this method has developed understanding of how lower and higher precursor values affect the morphology, structure, and optical properties of CexSn1?xO2 nanoparticles. CexSn1?xO2 nanoparticle synthesis involves a reaction between cerium and tin sources, namely, cerium nitrate hexahydrate and tin (II) chloride dihydrate, respectively, and the capping agent, polyvinylpyrrolidone (PVP). The findings indicate that lower x values yield smaller particle size with a higher energy band gap, while higher x values yield a larger particle size with a smaller energy band gap. Thus, products with lower x values may be suitable for antibacterial activity applications as smaller particles can diffuse through the cell wall faster, while products with higher x values may be suitable for solar cell energy applications as more electrons can be generated at larger particle sizes. The synthesized samples were profiled via a number of methods, such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FT-IR). As revealed by the XRD pattern analysis, the CexSn1?xO2 nanoparticles formed after calcination reflect the cubic fluorite structure and cassiterite-type tetrago-nal structure of CexSn1?xO2 nanoparticles. Meanwhile, using FT-IR analysis, Ce-O and Sn-O were confirmed as the primary bonds of ready CexSn1?xO2 nanoparticle samples, whilst TEM analysis highlighted that the average particle size was in the range 6?21 nm as the precursor concentration (Ce(NO3 )36H2O) increased from 0.00 to 1.00. Moreover, the diffuse UV-visible reflectance spectra used to determine the optical band gap based on the KubelkaMunk equation showed that an increase in x value has caused a decrease in the energy band gap and vice versa. 2021 by the authors. Licensee MDPI, Basel, Switzerland.